Role of intrinsic and supplemented antioxidants in follicular fluid: a shield against oxidative stress in oocyte health and embryo development - Gairola, Nidhi; Himanko Gogoi; Janhvi Dubey; Jasvinder Singh Khatiyaan; Harsh Chaudhary (Journal of Applied Pharmaceutical Research, 2025)
Background: In In Vitro Fertilization (IVF), a form of Assisted Reproductive Technologies (ART), the quality of oocytes and the successful development of embryos are crucial in determining the rate of fertility. The excessive presence of ROS (Reactive Oxygen Species) can cause oxidative stress, which negatively affects follicular fluid (FF) and oocyte maturation. Certain non-endogenous antioxidants, such as catalase, glutathione, and Superoxide Dismutase (SOD), are already present in Follicular fluid, which counterbalances these ROS and protects oocytes. Method: In addition to examining the possibility of exogenous supplements of antioxidants, such as vitamins C and E, and Coenzyme Q10 (CoQ10), this review investigates the function of these intrinsic antioxidants in maintaining oocyte health. Result: According to current in vivo and in vitro research findings done in mice, pigs, sheep, cows, and 18 patients in the age group(40±1), respectively, targeted antioxidant supplementation may enhance oocyte quality, embryo viability, and pregnancy outcomes. Conclusion: However, addressing individual heterogeneity in oxidative stress and optimizing dosage remains challenging. This review highlights how new antioxidant compounds and targeted interventions may enhance reproductive success by promoting cellular resilience in follicular fluid (FF). However, additional research into targeted antioxidant therapy in IVF is necessary.